Pengaruh Saham, Sukuk, Dan Reksadana Syariah Terhadap Pertumbuhan Ekonomi Indonesia Dengan Inflasi Sebagai Variabel Moderasi Periode 2012-2020 - Juni Kartika, Fidya; Zamzami, R. Mohd. (Jurnal Syntax Fusion, 2022)
This study aims to determine the effect of stocks, sukuk, Islamic mutual funds on Indonesia's economic growth with inflation as a moderating variable. The sample used in this study is quarterly report data from the Financial Services Authority for 9 (nine) years, namely from the first quarter of 2012 to the second quarter of 2020 for stocks, sukuk, and sharia mutual funds. Meanwhile, the rate of economic growth in Indonesia is seen from GDP and inflation using published report data from the Central Statistics Agency for 9 (nine) years from the first quarter of 2012 to the second quarter of 2020. The total sample data for this study were 34 quarterly data reports. The data collection method used is secondary data, which is data that is ready to be published by related parties or agencies and can be directly used by researchers. This study uses data taken from the statistical reports of the Financial Services Authority (OJK) and the Central Statistics Agency (BPS). The analysis technique used in this research is descriptive analysis, classical assumption test, multiple linear regression analysis, coefficient of determination test, f test and t test, Moderate Regression Analysis (MRA) with test tools namely Statistical Product and Services Solutions (SPSS) version 23.From the results of the analysis of the f test (simultaneous) shows that stocks, sukuk, Islamic mutual funds have a positive effect on Indonesia's economic growth. The results of the t test analysis (partial) show that Islamic stocks have a positive effect on Indonesia's economic growth, sukuk has a positive effect on Indonesia's economic growth, Islamic mutual funds have no effect on Indonesia's economic growth, inflation cannot moderate the relationship between Islamic stocks and Indonesia's economic growth, inflation does not can moderate the relationship between Sukuk and Indonesian Economic Growth. Inflation cannot moderate the relationship between Sharia Mutual Funds and Indonesian Economic Growth.